Pharmacological hypothesis: A recombinant probiotic for taming bacterial β‐glucuronidase in drug‐induced enteropathy - Manon Jardou; Clarisse Brossier; Kenza Guiyedi; Quentin Faucher; Roland Lawson (Pharmacology Research & Perspectives, 2022)
Abstract Advances in pharmacomicrobiomics have shed light on the pathophysiology of drug‐induced enteropathy associated with the therapeutic use of certain non‐steroidal anti‐inflammatory drugs, anticancer chemotherapies and immunosuppressants. The toxicity pathway results from the post‐glucuronidation release and digestive accumulation of an aglycone generated in the context of intestinal dysbiosis characterized by the expansion of β‐glucuronidase‐expressing bacteria. The active aglycone could trigger direct or indirect inflammatory signaling on the gut epithelium. Therefore, taming bacterial β‐glucuronidase (GUS) activity is a druggable target for preventing drug‐induced enteropathy. In face of the limitations of antibiotic strategies that can worsen intestinal dysbiosis and impair immune functions, we hereby propose the use of a recombinant probiotic capable of mimicking repressive conditions of GUS through an inducible plasmid vector.